Voltammetry in room temperature ionic liquids: comparisons and contrasts with conventional electrochemical solvents. - Barrosse-Antle, L; Bond, A; Compton, R; O'Mahony, A; Rogers, E; Silvester, D (2010)
The recent literature is surveyed to explore the nature of voltammetry in room temperature ionic liquids. The extent of similarities with conventional electrochemical solvents is reported and some surprising differences are noted.